2018
DOI: 10.1111/1365-2745.13038
|View full text |Cite
|
Sign up to set email alerts
|

Legacy effects of herbivory enhance performance and resistance of progeny plants

Abstract: Herbivory‐induced changes in plant resistance and tolerance traits can mediate the interaction between spatially and temporally separated above‐ and below‐ground herbivores. However, it is unknown how long the impact of transient herbivory events last or if legacy effects can be detected systemically in the plant and across plant generations. Here, we studied the impact of transient above‐ground herbivory by the specialist caterpillar Manduca sexta on the plant traits of wild tobacco Nicotiana attenuata and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 56 publications
2
16
0
Order By: Relevance
“…Studies have shown that the effect on the second herbivore is often larger when herbivores are separated in time, since the plant has had more time to respond (Denno et al, ; Erb, Robert, Hibbard, & Turlings, ). In addition, many responses diminish over time, and persistence of the response differs, both between responses and systems (Björkman, Dalin, & Ahrné, ; Kafle & Wurst, ). The effect of initial damage on the receiving herbivore might increase at first but over time decrease, creating a hump‐shaped relationship between time since initial damage and effect on the second herbivore.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the effect on the second herbivore is often larger when herbivores are separated in time, since the plant has had more time to respond (Denno et al, ; Erb, Robert, Hibbard, & Turlings, ). In addition, many responses diminish over time, and persistence of the response differs, both between responses and systems (Björkman, Dalin, & Ahrné, ; Kafle & Wurst, ). The effect of initial damage on the receiving herbivore might increase at first but over time decrease, creating a hump‐shaped relationship between time since initial damage and effect on the second herbivore.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, clarifying the overgrazing-induced legacy effects in plant defense strategies is critical for understanding processes occurring in grazing ecosystems. However, most previous studies on herbivory-induced legacy effects on plant defense strategies have focused on short-term insect herbivory, in contrast, studies examining long-term livestock grazing have received less attention by comparison (Holeski, Jander & Agrawal, 2012;Kafle & Wurst, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental disturbances (e.g., drought, herbivory) can have persistent effects on ecological attributes (e.g., ecological processes, community structure, population dynamics, and plant and soil characteristics) long after they occur (i.e., the legacy effect) ( Fox et al, 2015 ; Kafle & Wurst, 2019 ). Legacy effects are ubiquitous phenomena in nature and have been extensively studied in the context of plant succession, herbivory, invasive plants, ecosystem engineering, and human land use ( Cuddington, 2011 ; Kostenko et al, 2012 ; Wurst & Ohgushi, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about transgenerational effects induced by overgrazing in forage grass. According to a recent study by Kafle, Wurst & Dam (2019), single herbivory in the parental generation did not prime the transgenerational response, only sequential above-and below-ground herbivory did. Therefore, it can be speculated that transgenerational responses require a certain threshold of environmental stress.…”
Section: Legacy Effects Of Historical Grazing On Progeny Plantsmentioning
confidence: 92%